The influence of moral reasoning on adolescent decision-making and stress responses during VR social-moral conflict - Zhang, Jianbao; Zhang, Tingting (Frontiers in Psychology, 2025)
IntroductionMoral reasoning is a key component of moral development, yet its role in regulating stress during high-pressure social conflicts in adolescents is underexplored. This study investigated the influence of moral reasoning ability on decision-making and stress responses in Chinese adolescents during a simulated social-moral conflict.MethodsChinese adolescents (N = 118, 14–17 years) were grouped into high and low moral reasoning ability based on their Defining Issues Test-2 (DIT-2) scores. In a counterbalanced design, they were exposed to a high-pressure social-moral conflict scenario in immersive virtual reality (VR) and a neutral control condition. We measured physiological stress (heart rate), psychological stress (state anxiety), and moral decision-making (accuracy, speed).ResultsThe VR scenario successfully induced greater physiological arousal (higher heart rate) and state anxiety compared to the control condition. However, the level of moral reasoning ability had no significant effect on moral decision-making accuracy or state anxiety. A non-significant trend suggested that high-reasoning participants exhibited slightly lower average heart rates during the VR conflict, hinting at a potential stress-buffering effect.DiscussionThe findings indicate that the practical application of moral reasoning in adolescents is strongly moderated by situational pressures and developmental factors. While higher moral reasoning may not buffer against acute stress or improve immediate decision-making in intense social conflicts, this study highlights the value of VR for examining moral behavior in ecologically valid contexts. Future research with larger samples is needed to verify the potential stress-buffering trend.